Through the ever night - Rossi, Veronica (Rossi, Veronica., 2013)
It's been months since Perry was named Blood Lord of the Tides, and Aria was charged with an impossible mission; now they are about to be reunited. But their reunion is far from perfect. The Tides don't take kindly to Aria, a former Dweller. And with the worsening Aether storms threatening the tribe's precarious existence, Aria begins to fear that leaving Perry behind might be the only way to save them both.